KESEDIAAN, PERILAKU DAN KONSISTENSI ADOPSI E-COMMERCE KONSUMEN SAYURAN DI KOTA SEMARANG - Atik Maritasari; Marno Nugroho (Jurnal Ekonomi dan Bisnis, 2021)
The purpose of this study was to determine the main factors that influence the willingness, behavior and consistency of consumers in adopting vegetable consumer e-commerce in Semarang City. A total of 138 valid questionnaires were collected online from 16 sub-districts in Semarang City, resulting in a response rate of 92%. Data analysis used binary logistic regression. The results of this study indicate that 64% of vegetable e-commerce consumers have the same willingness and behavior, and 46% of consumers have willingness and behavior deviations. The main factors affecting willingness, behavior and consistency of e-commerce adoption of different vegetable consumers. The variables used consisted of perceived usefulness, perceived quality of logistics services, and distance to the nearest vegetable market which had a significant and positive effect on consistency of willingness to adopt, behavior and consistency of vegetable e-commerce behavior. The limitation of this research is only on vegetable consumers in the city of Semarang as the research object. Other cities in the vicinity can be used as a comparative study in further research. The main factors affecting differences in willingness and e-commerce behavior of vegetable consumers can be investigated. The implications of the results of this study can optimize the adoption of e-commerce in vegetable trade and contribute to an understanding of how to increase consumer awareness and participation in vegetable e-commerce. This research suggestion can be used to increase the e-commerce of vegetables in other cities that have the same problem.Keywords: e-commerce, willingness, behavior, consistency.